Does Sight Predominate Sound? Electrophysiological Evidence for Multisensory Mismatch Negativity Correlation - Horvath, J.C.; Schilberg, L.; Thomson, J. (Нейрофизиология, 2013)
When being presented with consistent and repetitive sensory stimuli, the human brain creates a predictive “memory trace” against which subsequent stimuli are compared. When later stimuli do not match this predictive model, a highly localized negative shift in the brain polarity occurs. This response, known as the mismatch negativity (MMN), is believed to represent a pre-attentive deviance-detection mechanism that serves to provide direct attention toward unanticipated events. At present, there are conflicting data as to whether visually generated and auditorily generated MMNs interact, or whether they are mediated by independent sensory-specific networks. We present compelling evidence that visual and auditory MMNs are strongly correlated, and that, upon presentation of dual-sensory “audiovisual” deviants, this synergy is heavily dictated by an individual’s unique visual response. This finding is suggestive of inhibitory interaction between the visual and auditory MMN networks. The characterization of this correlation helps one to explain (and explain away) much conflicting data published to date and opens the door to many questions regarding individual perception.